Thermodynamic Limit in High-Multiplicity Proton-Proton Collisions at s=7 TeV - Natasha Sharma; Jean Cleymans; Boris Hippolyte (Advances in High Energy Physics)
An analysis is made of the particle composition in the final state of proton-proton (pp) collisions at 7 TeV as a function of the charged particle multiplicity (dNch/dη). The thermal model is used to determine the chemical freeze-out temperature as well as the radius and strangeness suppression factor γs. Three different ensembles are used in the analysis: the grand canonical ensemble, the canonical ensemble with exact strangeness conservation, and the canonical ensemble with exact baryon number, strangeness, and electric charge conservation. It is shown that for the highest multiplicity class the three ensembles lead to the same result. This allows us to conclude that this multiplicity class is close to the thermodynamic limit. It is estimated that the final state in pp collisions could reach the thermodynamic limit when dNch/dη is larger than twenty per unit of rapidity, corresponding to about 300 particles in the final state when integrated over the full rapidity interval.